Solar‐Blind Ultrathin Sn‐Doped Polycrystalline Ga2O3 UV Phototransistor for Normally Off Operation. Issue 5 (23rd March 2022) - Yoon, Youngbin; Hwang, Wan Sik; Shin, Myunghun
Abstract : Deep ultraviolet (DUV) photodetectors (PDs) based on ultrawide bandgap β ‐Ga2 O3 have great potential for aerospace, military, and civilian applications, especially because of their inherent solar blindness. An 8 nm thick Sn‐doped polycrystalline β ‐Ga2 O3 semiconductor is used as the channel material for a solar‐blind PD in this study. The β ‐Ga2 O3 channel is fully depleted by upward bending of the energy band owing to the work function difference between the highly p‐type Si (gate electrode) and β ‐Ga2 O3, resulting in normally off behavior with a positive threshold voltage under dark conditions. The normally off behavior is beneficial for simplicity of the gate‐driver circuitry and low power consumption under standby conditions. The fully depleted 8 nm thick polycrystalline β ‐Ga2 O3 exhibits high‐performance DUV detection capability of light at 215 nm: a low dark current of 29.3 pA and high photo‐to‐dark‐current ratio of ≈10 4 at zero gate voltage. This fully depleted n‐type β ‐Ga2 O3 semiconductor with a wafer‐scale substrate can expedite the realization of high‐performance and low‐power‐consumption solar‐blind PDs. Abstract : Herein, an 8‐nm‐thick Sn‐doped polycrystalline β ‐Ga2 O3 semiconductor is used as the channel material for a solar‐blind photodetector. The β ‐Ga2 O3 channel is fully depleted, resulting in normally off behavior with a positive threshold voltage under dark conditions. The 8‐nm‐thick Sn‐doped polycrystalline β ‐Ga2 O3 photodetector exhibits a low dark current of 29.3 pA and hence a high photo‐to‐dark‐current ratio at zero gate voltage.